The Contribution of Non-Tropical Cyclone Vortices to the Rainfall of the Philippines - Olaguera, Lyndon Mark P (Archīum Ateneo, 2022)
Weaker disturbances than tropical cyclones (TCs) such as tropical depressions and cold surges can significantly induce heavy rainfall and flooding events over the Philippines. However, the analysis of these disturbances including their rainfall contributions are often neglected in previous studies. As the first attempt to address this research gap, this study investigates the rainfall contribution of non-TC vortices over the Philippines from 1979 to 2020. Only those rainfall-producing non-TC vortices that formed and appeared within a 500-km radius from the Philippine coastline were examined in this study. A total of 7,686 non-TC vortex days (50% of the total days during the analysis period) were identified. The mean rainfall contribution of these non-TC vortices was found to be highest over the northeastern Mindanao Island (80–90% of the mean daily rainfall) and lowest over the central and western regions of Luzon Island (50–60%). Seasonal analysis of the occurrence frequency of these vortices shows that they are most frequent during the December–February (DJF) season. In this season, the rainfall contribution may increase to 50–80% of the mean daily rainfall over the whole country, while in the other seasons, the rainfall contribution may only increase to as much as 60%. Higher frequency of extreme rainfall days associated with these non-TC vortices were also found during the DJF season. The frequency of occurrence and percentage rainfall contribution of these non-TC vortices in relation to the different phases of the Boreal Summer Intraseasonal Oscillation (BSISO) during boreal summer (June–October) and the Madden–Julian Oscillation (MJO) during boreal winter (December–April) were also examined. Higher frequency and percentage rainfall contribution over the country were found during Phases 4–6 of both the BSISO and MJO, during which their respective active convections transition from the Maritime Continent to the western North Pacific.